👤

x) ( x + 8 × 2 + 6 × 8) - 8 × 9 + 8 × 8 = 6× 10 + 2 × 4
Va rog mult


Răspuns :

( x + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 6 × 10 + 2 × 4

( x + 16 + 48 ) - 72 + 64 = 60 + 8

( x + 64 ) - 72 + 64 = 68

( x + 64 ) - 72 = 68 - 64

( x + 64 ) - 72 = 4

x + 64 = 72 + 4

x + 64 = 76

x = 76 - 64

x = 12
( X + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 68

( X + 8 × 2 + 6 × 8 ) - 72 + 64 = 68

( X + 8 × 2 + 6 × 8 ) - 72 = 68 - 64

( X + 8 × 2 + 6 × 8 ) - 72 = 4

X + 8 × 2 + 6 × 8 = 72 + 4

X + 16 + 48 = 76

X + 16 = 76 - 48

X + 16 = 28

X = 28 - 16

X = 12

sper ca te-am ajutat!